CD66b+ neutrophils and α‐SMA+ fibroblasts predict clinical outcomes and benefits from postoperative chemotherapy in gastric adenocarcinoma. (25th February 2020) - Cong, Xiliang; Zhang, Yongle; Zhu, Ziyu; Li, Sen; Yin, Xin; Zhai, Zhao; Zhang, Yu; Xue, Yingwei
Abstract: Background: Emerging evidence indicates that the tumor microenvironment (TME) influences tumor progression through the various cells it contains. Tumor‐associated neutrophils (TANs) and cancer‐associated fibroblasts (CAFs) are prominent constituents of diverse malignant solid tumors and are crucial in the TME and cancer evolution. However, the relationships and combined prognostic value of these two cell types are not known in gastric adenocarcinoma (GAC). Materials and Methods: In total, 215 GAC patients who underwent curative surgery were enrolled. TANs were assessed by immunohistochemical staining for CD66b, and CAFs were evaluated by immunohistochemical staining for α‐smooth muscle actin (α‐SMA). Results: The percentages of patients with high‐density TANs and CAFs in GAC tissue were 47.9% (103/215) and 43.3% (93/215), respectively. The densities of TANs and CAFs in GAC tissue samples were markedly elevated and independently correlated with GAC clinical outcomes. A strong correlation ( R  = .348, P  < .001) was detected between TANs and CAFs in GAC. The combination of TANs and CAFs produced a more exact outcome than either factor alone. Patients with an α‐SMA low CD66b high (hazard ratio [HR] = 1.791; 95% CI: 1.062‐3.021; P  = .029), α‐SMA high CD66b low (HR = 2.402; 95% CI: 1.379‐4.183; P  = .002), or α‐SMA high CD66b high (HR = 3.599; 95% CI: 2.330‐5.560; P  < .001) phenotype were gradually correlated with poorer disease‐free survival than the subset of patients with an α‐SMA low CD66b low phenotype. The same results were observed for disease‐specific survival in the subgroups. Noticeably, in stage II‐III patients with the α‐SMA low CD66b low phenotype, an advantage was obtained with postoperative chemotherapeutics, and the risk of a poor prognosis was reduced compared with stage II‐III patients with the α‐SMA low CD66b high, α‐SMA high CD66b low or α‐SMA high CD66b high phenotype (HR: 0.260, 95% CI: 0.124‐0.542, P  < .001 for disease‐free survival; and HR: 0.258, 95% CI: 124‐0.538, P  < .001 for disease‐specific survival). Conclusion: Overall, we concluded that the combination of CD66b + TANs and α‐SMA + CAFs could be used as an independent factor for patient outcomes and to identify GAC patients who might benefit from the administration of postoperative chemotherapeutics. Abstract : We concluded that the combination of CD66b + tumor‐associated neutrophils and α‐SMA + cancer‐associated fibroblasts could be used as an independent factor of outcome and to identify those gastric adenocarcinoma patients who might obtain advantage from postoperative chemotherapeutics.